Learning together through coteaching coaching: A model of support for coteaching pairs in clinical practice. (April 2021) - Guise, Megan; Hegg, Sarah; Robbins, Amy
Abstract: This qualitative study explores coteaching as a model for the teacher education clinical experience, examining how coteaching coaching serves as a support to enhance pair (pre- and in-service teacher) understanding of coteaching. Through the analysis of coteaching observations, coaching session discourse, and interviews with coteaching pairs, the authors posit that coteaching coaching provides a space for both teachers to be positioned as learners and engage in critical analysis of coteaching. For this positioning and engagement in coteaching to occur, coaching sessions should occur frequently with the coach adopting a stance that balances critical feedback and collaborative inquiry. Highlights: Coteaching pair support is needed to enhance implementation. Coteaching coaching works best if both coteachers are positioned as learners. Coteaching coaching provides a space for reflection and goal setting.